Memorable Tourism Experience Moments and Lasting Pride: The Impact of Hiking Experiences on Revisit Intentions - Berutu, Meta Bara; Sari, Dewi Agustin Pratama; Febrilia, Ika; Krissanya, Nofriska; Ahmad, Siti Noor Bayaah; Cindy, Vera Deyana (Journal of Business and Behavioural Entrepreneurship, 2024)
What makes hikers feel satisfied and want to return? This research identifies factors that contribute to a memorable hiking experience, focusing on the role of emotions such as pride and intention to repeat visits to outdoor activities. The use of these variables addresses a research gap about limitation to use pride variable that is rarely used even though they have a significant effect on tourism activities. This research aims to study how the unique tourism experience, pride, and overall hiking enjoyment correlate. Data collection in this research was 142 respondents throughout Indonesia who had done hiking. Data is processed using PLS-SEM, which can overcome the minimal number of respondents. The results of this research state that pride has a significant influence on MTE, as well as the relationship between pride and revisit intention. However, it differs from the relationship between MTE and revisit intention, which has an insignificant effect. This research recommends that emotion is a big attraction that can influence tourists’ future choices. Therefore, to create opportunities for valuable experiences, stakeholders invest in infrastructure and establish an image built to know the hiker profile and customize individual experiences.